Business finance and Philippine business firms - San Gabriel, Nati C. (Quezon City, Philippines : Goodwill Trading Co, Inc., 1980)
Textbook writings is an art that seeks to condense the wealth of information on a subject into a comprehensive, easy to read, easy to understand literature
Business and finance -- Organizing a business -- Business organization -- Financial concepts and tools -- Working capital -- Sources of short-term capital -- Corporate stocks -- Corporate bonds -- Extinction of bounded debts -- Capital budgeting -- Intermediate and long term capital -- Planning capital structure -- The Capital market -- Secondary markets
Includes bibliographical references.
Keywords: FINANCE -- PHILIPPINES